2022
DOI: 10.3171/2021.11.jns212137
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of immediate and long-term remission after initial transsphenoidal surgery for acromegaly and outcome patterns during follow-up: a longitudinal study on 659 patients

Abstract: OBJECTIVE Treatment outcomes following initial transsphenoidal surgery (TSS) for acromegaly are erratic. Identifying outcome patterns can assist in informing patients about possible treatment outcomes and planning for individualized adjuvant treatments in advance. In this study, the authors aimed to investigate the immediate and long-term endocrine remission rates following initial TSS for acromegaly, identify clinical determinants of treatment outcomes, and explore outcome patterns during a long-term follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…For example, some studies reported approximately 60% of patients achieve biochemical remission in the immediate postoperative period when defined as nadir GH < 1 µg/L during OGTT, with lower rates in patients with macroadenomas and in those treated with a microscopic approach [ 65 , 66 ] (MQ). However, remission rates fell to approximately 40% when using stricter criteria of < 0.4 µg/L on postoperative day 2, and 20% of patients achieved GH below threshold after a delayed period of a median of 24 months of observation [ 67 ] (LQ). Of note, very early (and tighter) GH control might be predictive of later GH outcome, as nadir GH > 0.4 µg/L on postoperative day 2–5 predicted lack of remission after a mean follow-up of 44 months [ 68 ], and nadir < 0.4 µg/L at 2–5 days and at 3–6 months correlated better with remission than did < 1 µg/L [ 68 , 69 ] (LQ).…”
Section: Criteria For Remissionmentioning
confidence: 99%
“…For example, some studies reported approximately 60% of patients achieve biochemical remission in the immediate postoperative period when defined as nadir GH < 1 µg/L during OGTT, with lower rates in patients with macroadenomas and in those treated with a microscopic approach [ 65 , 66 ] (MQ). However, remission rates fell to approximately 40% when using stricter criteria of < 0.4 µg/L on postoperative day 2, and 20% of patients achieved GH below threshold after a delayed period of a median of 24 months of observation [ 67 ] (LQ). Of note, very early (and tighter) GH control might be predictive of later GH outcome, as nadir GH > 0.4 µg/L on postoperative day 2–5 predicted lack of remission after a mean follow-up of 44 months [ 68 ], and nadir < 0.4 µg/L at 2–5 days and at 3–6 months correlated better with remission than did < 1 µg/L [ 68 , 69 ] (LQ).…”
Section: Criteria For Remissionmentioning
confidence: 99%
“…Clearly, transsphenoidal endoscopic surgery by a senior surgeon and increased surgical experience is important for improving remission rates [31]. Age and sex are predictive of postoperative remission rates in some studies [32][33][34]. But their results were inconsistent and more research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…This was a retrospective study conducted at Peking Union Medical College Hospital (PUMCH). PUMCH is the China Pituitary Disease Registry Center and China Pituitary Adenoma Specialist Council and leads clinical practice and research studies in the field of MDTs for PAs in China [ 17 21 ].…”
Section: Methodsmentioning
confidence: 99%